PENGARUH TINGKAT LOAN TO DEPOSIT RATIO (LDR) TERHADAP PROFITABILITAS PADA PT BANK X (Periode tahun 2008-2012) - Widjaja, Yani Restiani (www.bsi.ac.id, 2014)
Bank is a financial institution that serves as a financial intermediary which means collecting funds from the public and distribute it back to the community in the form of loans. The purpose of this study was to determine whether there is a significant influence and how much influence the Loan to Deposit Ratio (LDR) to Bank Profitability expressed by Return on Assets (ROA).The method used in this research is deskriptife with the survey approach. While to analyze the data, used a quantitative approach, namely the technique of correlation analysis and simple linear regression analysis as a tool for the calculation.From the research, the regression equation is Y = 0.083 +0.706 X. Keywords: Loan to Deposit Ratio (LDR), Bank Profitability,Return on Asset (ROA)